PERANCANGAN ARCHITECTURE ENTERPRISE PADA LEMBAGA MTS DINIYAH PUTRA PONDOK PESANTREN SYALAFIYAH-SYAFI’IYAH MENGGUNAKAN METODE(ENTERPRISE ARCHITECTURE PLANNING TOGAF ADM) - Akhlis Munazilin; Fiki Hasan; Moch. Fajar; Moch Ibrahim Valentino (CV. Denasya Smart Publisher, 2025)
MTS DINIYAH PUTRA Salafiyah Syafi'iyah Islamic Boarding School as one of the formal educational institutions in the Salafiyah Syafi'iyah Islamic Boarding School with its own characteristics. MTS DINIYAH PUTRA Salafiyah Syafi'iyah Islamic Boarding School is designed as a full boarding school. The educational program is designed to produce a leading boarding school in developing the potential of students in the academic, religious, and skills fields with discipline as a foundation to be able to compete at the national and international levels. This study aims to design an Enterprise Architecture model and implement the roadmap made to make it easier to develop information system architecture in educational institutions in the future. Researchers conducted research at MTS DINIYAH PUTRA Salafiyah Syafi'iyah Islamic Boarding School. From the results of the study, a business process design was obtained in activities at MTS DINIYAH PUTRA Salafiyah Syafi'iyah Islamic Boarding School using Enterprise Architecture Planning TOGAF ADM with the Value Chain model. The research results can be known about the environment of the business process system at MTS DINIYAH PUTRA, Salafiyah Syafi'iyah Islamic boarding school, which consists of three main activities, namely PPDB, Teaching and Learning Activities, graduation and alumni.